Investigation and fabrication of asymmetrical supercapacitor using nanostructured Mn3O4 immobilized carbon nanotube composite. (February 2020) - Ranjithkumar, R.; Arasi, S. Ezhil; Nallamuthu, N.; Devendran, P.; Lakshmanan, P.; Arivarasan, A.; Kumar, M. Krishna
Abstract: The manganese oxide (Mn3 O4 ) nanoparticles (NPs) were immobilized in the surface of functionalized carbon nanotubes (fCNT) (Mn3 O4 –fCNT composite) for the enhancement of electrochemical performances. The broad and notable crystalline peaks were found in a powder X-ray diffraction pattern of Mn3 O4 –fCNT and it confirms that, Mn3 O4 presence in nanoscale. The functional vibrations of –OH, –COOH, CO, C–O were found in FTIR spectrum and Raman spectra also recorded to understand functional groups present in the composite. The surface morphology was studied and also, the elemental analysis was carried out for Mn3 O4 –fCNT using SEM images of the composite. The electrochemistry responses of Mn3 O4 –fCNT were investigated. We have evaluated its response and performances in cyclic voltammetry, impedance, galvanostatic charge-discharge aspects. A notable specific capacitance of 499 Fg -1 at 0.1 mAg −1 was found in Mn3 O4 -fCNT. The asymmetrical supercapacitor was designed with Mn3 O4 –fCNT and ZnO-CNT and its specific capacitance was evaluated. Graphical abstract: Design of Mn3 O4 –CNT and ZnO–CNT asymmetrical supercapacitor and its cyclic voltammetry curves. Image 10551 Highlights: Mn3 O4 −fCNT/ZnO-CNT composite based asymmetrical supercapacitor was fabricated. Mn3 O4 −fCNT composite exhibits the specific capacitance about 499 F/g. Power density of 4500 W/kg was found for Mn3 O4 −fCNT nanocomposite. ¾ times of specific capacitance retention after 1000 cycles was found. Power density of 2200 W/kg aas found for asymmetrical supercapacitor.